Genome-derived cytosolic DNA contributes to type I interferon expression and immunogenicity of B-cell lymphoma cells. Issue 2 (December 2015) - Shen, Yu J.; Ho, Samantha S.W.; Tan, Nikki Y.; Koo, Christine Xing'Er; Khatoo, Muznah; Cheung, Florence S.G.; Gasser, Stephan
Highlights Genome-derived ssDNA, dsDNA and DNA:RNA hybrids are present in the cytosol of tumor cells. Cytosolic DNA can potentially form non-B DNA structures. Cytosolic DNA contributes to type I interferon-dependent immune rejection of B-cell lymphoma.